2008
DOI: 10.1038/gt.2008.59
|View full text |Cite
|
Sign up to set email alerts
|

In vivo transfer of plasmid from food-grade transiting lactococci to murine epithelial cells

Abstract: We recently demonstrated that noninvasive food-grade Lactococcus lactis (L. lactis) can deliver eukaryotic expression plasmid in mammalian cells in vitro. Here, we evaluated, in vivo, whether a eukaryotic expression plasmid carried by lactococci can translocate to the epithelial cells of the intestinal membrane. The strain LL(pLIG:BLG1) carrying one plasmid containing a eukaryotic expression cassette encoding b-lactoglobulin (BLG), a major allergen of cow's milk, was orally administered by gavage to mice. BLG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 39 publications
4
46
0
Order By: Relevance
“…We demonstrated previously for the first time that a fully functional plasmid can be transferred with low efficiency from a LAB transiting in the gut to intestinal cells: the oral administration of L. lactis strains carrying a plasmid containing a eukaryotic BLG expression cassette elicited transitory BLG production by the epithelial cells of the intestinal wall. Mice treated with this noninvasive strain developed a BLG-specific T H 1 immune response and were protected from further sensitization (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated previously for the first time that a fully functional plasmid can be transferred with low efficiency from a LAB transiting in the gut to intestinal cells: the oral administration of L. lactis strains carrying a plasmid containing a eukaryotic BLG expression cassette elicited transitory BLG production by the epithelial cells of the intestinal wall. Mice treated with this noninvasive strain developed a BLG-specific T H 1 immune response and were protected from further sensitization (2).…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed (i) that native L. lactis can deliver a eukaryotic expression cassette coding for the bovine ␤-lactoglobulin (BLG), one of the major cow's milk allergens, into mammalian epithelial Caco-2 cells, and (ii) that these cells were able to express and secrete BLG protein in its native conformation (10). Recently, we demonstrated the ability of native noninvasive L. lactis to deliver a fully functional plasmid to murine intestinal cells in vivo (2).…”
mentioning
confidence: 99%
“…Thus, the scientific community has recently explored the use of non-pathogenic bacteria, such as L. lactis, as prophylactic or therapeutic tools and, more recently, as DNA delivery vehicles for genetic immunization (Wells and Mercenier, 2008;Pontes et al, 2011). Chatel et al (2008 showed that L. lactis could deliver a plasmid to epithelial cells of the intestinal membrane in conventional mice.…”
Section: Discussionmentioning
confidence: 99%
“…Lactococcus lactis has been proposed as a being a safe and effective vaccine platform for the delivery of therapeutic molecules to the immune system (Nouaille et al, 2003;Pontes et al, 2011). It has been shown that wild-type (wt) L. lactis can deliver DNA vaccines both in vitro and in vivo after oral inoculation of mice (Guimarães et al, 2005;Chatel et al, 2008). However, the ratio of DNA transferred to mammalian cells was quite low.…”
Section: Introductionmentioning
confidence: 99%
“…Development of phagemid vectors, plasmids with a bacteriophage origin of replication that are packaged into phage particles upon the addition of helper phages, has made the genetic manipulation of bacteriophages as easy as manipulating plasmids used in the production of viral vectors [67]. The phagemid system allows for precise control over the relative composition of wild-type and modified coat proteins [68] while eliminating potentially immunogenic genes encoding bacteriophage proteins. The bacteriophage coat proteins can be engineered to incorporate targeting ligands without significantly affecting structure.…”
Section: Bacteriophagesmentioning
confidence: 99%